FARMING TECHNOLOGY ADOPTION FOR CATTLE BUSINESS RESOURCE DEVELOPMENT - Umboh, Sintya J. K (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2024)
The decline in cattle prices can increase the demand for cattle, but the supply of fattened cattle will receive low cattle prices and have an impact on decreasing income. The usual strategy used to deal with changes in beef cattle prices in order to obtain higher prices was to postpone sales until prices rise again. Delaying sales causes additional total production costs, which can affect income. The introduction of the application of cattle farming business development technology was carried out as an effort to make it easier for farmers to calculate the income and profits from their cattle farming business. In this case, farmers were introduced to a system for calculating costs and income from cattle fattening businesses using the Visual Basic computer program. This application was a method for calculating the profits that can be obtained from a cattle farming business carried out by small-scale cattle farmers. This system was created to make it easier for a farmer to calculate the development of his cattle farming business. The results of the analysis showed an adoption rate of 72.84, which means that 72.84 percent of the introduction of technology was adopted by farmers. This indicates that the implementation of this price information technology was well received by farmers because it was considered to have a positive impact on the household economy and the development of sustainable cattle farming business resources.